PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL MELUKIS TEKNIK AQUAREL DI SMA NEGERI 3 SURAKARTA TAHUN AJARAN 2020 - Agung Nugroho, Muhammad Faizal; hida, Adam Wa; na, Mar ga (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Paint with aquarel technique is the art of painting that use watercolour and has been applied as teaching system in school. Painting with aquarel technique can build imagination and be a sign of art to reveal student’s ideas and concepts. But of ten student can not make the paint with aquarel technique maximally, so with this tutorial media hopefully can be the alternatives for students who have attractions about paint with aquarel technique but do not have acces to get aquarel technique materials wich is equipped with media tutorial that efficient and ideal. This article use literature reviews wich is contains theory or previous researches related watercolour painting and the benefits of using video tutorial media. Video tutorial media with aquarel technique expected to be able to help the teachers to providing opportunities for students to learn paint with ideal learning media effective and efficient.